Implementation of the KOTAKU Program: Case Study in Kendari - Andi Muhammad Bathari; Rekson Solo Limba; La Ode Mustafa (Journal Publicuho, 2018)
ABSTRACTThis study aimed to find out and analyze program implementation cities without slums in handling slum houses in Kendari, as well as to investigate and analyze what factors influence implementation city programs without slums in handling slum houses in Kendari. The design of research is descriptive qualitative, the technique of determining internal informants this research is using purposive sampling technique and set at 10 informants. The data collection technique used in this study is a technique observation, interviewing techniques, and documentation. Data analysis techniques in this study was a descriptive data analysis technique, through the technical stages of interactive analysis including reduction data, data presentation and conclusion. The results of this study indicated that the implementation of the KOTAKU program in Kendari, which included improved sanitation, repaired to uninhabitable homes and provision Clean water had been running, but it had not been fully implemented according to the target because of it the program is 100-0-100 and the target of free slum in 2019 has not been achieved. Implementation of the KOTAKU program in Kendari was influenced by four factors which included Communication, Disposition, Resources, and Bureaucratic Structure. All of these factors were resulting in a lack of maximum implementation of the KOTAKU program in Kendari.    Keywords: Implementation, Program, No Slum City (KOTAKU)